Extension education impacts of farming systems research in Lesotho - Youmans, David Vance (University of the Free State, 1986)
Farming systems research is an approach to agricultural development in which farmers join scientists in mutual, interdisciplinary problem solving activities on farmers' lands, In that context,· extension education, a nonformal mode developed in the agricultural setting, plays a central and vital role in the dissemination of information and the diffusion of innovations. The farming systems research and extension strategy has been at work in Lesotho since 1979 as a fully integrated policy in the Research Division of the Ministry of agriculture and Marketing. Funded by the United States Agency for International Development, faculty members of Washington State University have worked as advisors and colleagues with national officers and members of farming communities in carrying out appropriate activities; Extension education programmes have been conducted among· a number of clienteles since 1981, addressing such areas of need as rural organization, village leadership, extension methods, and technical agriculture from a variety of fields and at several levels of instruction. Members of organized farmer contact groups as participants and diffusors, village chiefs and headpersons, and government extension workers and subject matter specialists were three key target groups for extension education programmes. This study concentrated on a threefold task. First, it undertook to review and substantiate the role and dynamics of extension education in agricultural development, in general and as reflected in farming systems research activities in Lesotho, Second, it sought to assess the impacts of extension education programmes in the above context in terms of changes in knowledge, attitudes, skills, aspirations (KASA), agricultural practices and, where possible, end results, using a reflective appraisal of programmes (RAP) methodology to ascertain those outcomes. Third, it expected to formulate conclusions and advance recommendations for the improvement of future such programmes based on the evidence thus derived, together with any other discoveries made during the course of the study. In basing this research on the 1979 - 1984 segment 9f the farming systems research intervention in Lesotho, and in seeing it through to its contemplated closure the researcher · concludes that the outcomes demonstrate that there have been impressive, at times dramatic, KASA changes among the three key clienteles perceived by their members as directly related to the extension education programmes under study. Likewise, practice change in all three groups, while more variable, was significant as vividly described by the participants themselves. Finally, end results, best seen among the farmer contact groups, disclosed such real benefits as better meals for families, higher crop yields, improved condition of animals and increased incomes. The members of those same farmers groups had become effective disseminators and diffusers, reaching nearly nine other farmers each. It is further concluded that, while farming systems research is neither a panacea for low productivity nor a blueprint for Africa, it is a useful and dynamic development strategy, and that, as in other strategies, extension education is both central and critical to dissemination of information and diffusion of innovations. Extension education programmes, designed according to available resource levels, do produce positive change in participants' learning, practical behaviour and end benefits. Women, as a dynamic human resource in the development formula, must be considered in the design and delivery of extension programmes. And, urgent research into extension education for the developing world is required so that new flexible and realistic methodologies might be perfected to meet the challenge of the millennium.
Thesis (D.Ed. (History of Education and Comparative Education))--University of the Free State, 1986
Keywords: Agriculture; Agricultural expansion work; Agriculture -- Lesotho